Marketing Islamic banking products: Malaysian perspective - Kamarulzaman, Y.; Madun, A. (Emerald, 2013)
Purpose – The rapid growth of Islamic banking in Malaysia warrants banking institutions being more proactive and innovative in marketing their products. The purpose of this paper is to re‐evaluate the progress and achievements of Islamic banking in Malaysia, particularly in the area of sales and marketing of Islamic banking services.